A validated approach for probabilistic structural integrity design code implementation. (November 2021) - Chavoshi, Saeed Zare; Bradford, Rick; Booker, Julian
Highlights: A simple approach for incorporating probabilistic structural integrity assessment is proposed. The approach is validated using real EDF nuclear plant case-studies. The approach is not restricted to a particular failure mechanism and material. Monte Carlo probabilistic assessment based on R5V2/3 is conducted. Abstract: This paper provides a possible approach for incorporating probabilistic structural integrity assessment which is sufficiently simple to encourage its adoption by design engineers. The approach, called the "Three-Term Reference Damage Model (3T-RDM)", is developed in the context of a particular benchmark problem and a proposed Design Chart where the probability of crack initiation by creep-fatigue in a widely used material in nuclear plants, namely 316H austenitic stainless steel, is estimated based on the R5V2/3 high temperature procedure. In principle, the 3T-RDM is not restricted to a particular failure mechanism, i.e., fracture, creep rupture, creep-fatigue crack initiation and growth are all within its scope, and non-metallic materials may also be addressed. To further validate the accuracy and generality of the proposed 3T-RDM and Design Chart, deterministic and Monte Carlo probabilistic structural integrity assessments are conducted for three EDF nuclear plant case-studies and the results are superimposed on the Design Chart obtained from the benchmark problem. The analysis indicates an excellent consistency between the results, justifying the adoption of the 3T-RDM for an intermediate level of probabilistic assessment in the nuclear sector.